The stability and removal of water-dispersed CdSe/CdS core-shell quantum dots from water. (October 2017) - Chen, Xu; Ok, Yong Sik; Mohan, Dinesh; Pittman, Charles U.; Dou, Xiaomin
Abstract: The increasingly wide use of semiconductor nanocrystals inevitably leads to their release into aquatic environment. The aggregation behaviors of 3-mercaptopropionic acid-capped CdSe/CdS core-shell quantum dots (MPA-QDs) under various water chemistry conditions were examined and their removal using Fe 3+ and Al 3+ coagulants was evaluated. Cationic species rather than concentrations affected the stability of MPA-QDs. Adding 2 mM Ca 2+ led to a much larger ζ-potential decrease and particle size increase than adding 150 mM K + at each tested solution pH. This indicated that complexation and depletion of surface-bound carboxyl groups by divalent Ca 2+ has a more pronounced effect than compression of the electrical double layer by high concentrations of monovalent K + . The presence of humic acid increased the stability of MPA-QDs, which might increase negative surface charging via overcoating or bind to the surface of MPA-QDs. The nanoparticles exhibited similar aggregation kinetics patterns in tap water and seawater, but varying patterns in the lake water because of the co-existence of 2.3 mM total of Ca 2+ and Mg 2+ . MPA-QDs (5 mg L −1 ) were readily coagulated by 2.4 mM Al 3+ or 1.2 mM Fe 3+ in tap water. Al 3+ and Fe 3+ can bind with carboxyl groups of the surface capping ligands, neutralize the negative charges on the surface of MPA-QDs and decrease the electrostatic repulsion forces to induce MPA-QDs aggregation. In addition, MPA-QDs could be bound with and wrapped into the flocs of hydrolysis products of coagulants. The results reported here could help broaden our understanding of the impacts and remediation of water-dispersed core-shell QD nanoparticles. Highlights: The stability, aggregation and remediation of core/shell QDs were evaluated. Ca 2+ led to severe aggregation of soluble QDs than K + at much lower concentrations. Depletion of surface bound ligand has a more pronounced effect than compression EDL. QDs exhibited different aggregation patterns in tap water, seawater and lake water. Both Fe 3+ and Al 3+ were able to remediate QDs from water but the former was better.